From ROS to Tumorigenesis: Understanding the Oxidative Pathways in Cervical Cancer Progression - Mahdi, Montadher Ali; Dawood, Yasser Jassim; Jumaa, Azal Hamoody; Abod, Kareem Salim; Manssor, Karrar Jabbar (Asian Pacific Journal of Cancer Biology, 2026)
Cervical cancer remains a leading cause of cancer-related morbidity and mortality among women worldwide. Although persistent infection with high-risk human papillomaviruses (HPV) constitutes the principal etiological agent, accumulating evidence implicates oxidative stress as a pivotal co-factor in the initiation, promotion, and progression of cervical carcinogenesis. Reactive oxygen species (ROS), generated endogenously and exogenously, inflict cumulative genetic and epigenetic alterations, foster a pro-inflammatory tumor microenvironment, and promote malignant transformation. While endogenous antioxidant defense mechanisms initially mitigate ROS-mediated damage, their failure or exhaustion during disease evolution facilitates tumor progression and therapeutic resistance. This review critically examines the intricate interplay between oxidative stress and antioxidant responses throughout the stages of cervical cancer development. Furthermore, it explores emerging redox-targeted therapeutic strategies, emphasizing the dualistic role of antioxidants in cervical neoplasia and the challenges of modulating oxidative balance in clinical settings. A deeper understanding of redox dynamics may inform novel preventive and therapeutic interventions against cervical cancer.